Connectivity of the sea urchin Diadema mexicanum A. Agassiz, 1863 (Echinoidea, Diadematidae) in the Pacific coast of Costa Rica - Carvajal Rojas, Sofía (2025)
Diadema mexicanum is essential for controlling algae and maintaining coral dominance on coral reefs. Despite its importance as a key grazing species, little is known about the genetic structure and connectivity of its populations. Molecular markers are particularly sensitive to genetic differences between disjunct populations, providing insight into their resilience to environmental changes. This study seeks to genetically characterize D. mexicanum populations on coral reefs along the Pacific coast of Costa Rica. Sampling took place between May and October 2019. DNA was extracted from each sample, and microsatellite markers were subsequently amplified using primers designed for D. antillarum and Strongylocentrotus nudus. Data analysis was performed using GeneMarker, R Studio, and Structure. The analysis revealed lower genetic diversity than previously reported for these microsatellites, resulting in high inbreeding coefficient values. This could be attributed to several factors, such as high reproductive success variation and null alleles. A weak genetic structure was found among sampling sites, but this structure was independent of the region where samples were collected. No isolation by distance was detected, suggesting genetic connectivity and gene flow within populations. Future studies would benefit from analyzing a wider range of molecular markers and ensuring more equitable sampling across sites.